Effect of in-situ moisture conservation practices on yield and economics of sunflower and pigeonpea intercropping in Vertisols of Northern Karnataka: Effect of in-situ moisture conservation practices on yield and economics of sunflower and pigeonpea intercropping in Vertisols of Northern Karnataka - AMRULLAH RAHIL; M R UMESH; VIKAS KULKARNI; N ANANDA; B M CHITTAPUR; ARUNKUMAR HOSAMANI (Journal of Oilseeds Research, 2023)
Field experiments were conducted during Kharif 2020 and 2021 to study the effect of in-situ moisture conservation practices on yield and economics of sunflower and pigeonpea intercropping in Vertisols of Northern Karnataka. Treatments consisted of broad bed and furrow, ridges and furrow, tied ridging, conservation tillage, flatbed and opening furrow after every three rows at 30 DAS compared with flatbed sowing as main plots. Treatments in sub plots were sunflower + pigeonpea (1:1), sole pigeonpea and sunflower. Results showed that significantly higher yield and yield attributes of sunflower and pigeonpea were recorded in ridges and furrows followed by tied ridges and furrow. Yield of both the crops were significantly more in respective sole crops over the intercropping. Higher SEY, LER, net return and BC ratio were noticed in ridges and furrow under intercropping.